2 × ( a + b ) = ( a - b ) + 100
a + b = 3 × ( a - b)
2 × 3 × ( a - b ) = a - b + 100 → am inlocuit in prima relatie pe a + b
6 a - 6 b - a + b = 100
5 a - 5 b = 100 ⇒ 5 × ( a - b ) = 100 ⇒ a - b = 100 : 5 = 20
a + b = 3 × 20 = 60
Avem relatiile:
a + b = 60 → suma numerelor
a - b = 20 → diferenta numerelor ⇒ a = b + 20
b + 20 + b = 60 → am inlocuit pe a cu b + 20
2 b = 60 - 20 ⇒ b = 40 : 2 ⇒ b = 20 → al doilea numar
a = 20 + 20 = 40 ⇒ a = 40 → primul numar
verific: 2 × ( 40 + 20 ) > 40 - 20 cu 100
120 > 20 cu 100